Relationship between the Geotourism Potential and Function in the Polish Part of the Roztocze Transboundary Biosphere Reserve - Teresa Brzezińska-Wójcik (Geosciences, 2021)
The Polish part of the Roztocze Transboundary Biosphere Reserve area is characterized by diversified geotourism resources with relatively high value. However, their potential seems not to be fully used in the current product offer. The aim of the study was therefore to assess the spatial variability of the geotourism potential and function and to determine their interrelations in view of further development of geotourism in the Roztocze TBR and the perspective of creation of the “Kamienny Las na Roztoczu” geopark. The study was carried out with the use of the taxonomic method of multidimensional comparative analysis consisting of calculation and analysis of general, total, and partial indices of the geotourism potential and function in 22 communes. The results showed the highest total indicator of geotourism potential in two communes, i.e. Józefów and Krasnobród, and the highest value of the total geotourism function index in Krasnobród. The results of the analysis of the relationships between the geotourism potential and function indicate that the geotourism resources and products are fully used in terms of the development of the function only in Krasnobród commune. In turn, the value of the total geotourism function index in the Zwierzyniec commune exceeds the geotourism potential indicator, which implies that this area is overloaded by tourist movement. The total indicators of geotourism potential in the other communes, especially Józefów, Krasnobród, Lubycza Królewska, and Susiec, indicate the possibility of more intensive exploitation of geotourism resources in preparation of interesting products in compliance with the principles of sustainable development and, consequently, the development of the geotourism function.